Figueroa modified presurgical nasoalveolar molding for cleft patients: A case series of three cases - Divya Doneria; Seema Thakur; Anika Uppal; Alka Chauhan (Wolters Kluwer Medknow Publications, 2018)
Presurgical nasoalveolar molding (PNAM) is a modified approach of presurgical infant orthopedics for cleft lip and palate (CLP) patients. PNAM provides the advantage of reduction in the nasal deformity along with reduction in the severity of the alveolar defect before surgery. Nonsurgical nasal correction, achieved by nasoalveolar molding, helps the surgeon to achieve better postoperative finer surgical scar, good nasal tip projection, and more symmetrical nasolabial complex. This clinical case report presents a series of three cases of a child with CLP, two with complete unilateral, and one with incomplete bilateral. These cases were treated with Figueroa modified PNAM technique before primary lip repair surgery.